Investigation of variations and trends in TSP concentrations in the Klang Valley region, Malaysia - Mohamed Elnour Yassen; Jamaluddin Md. Jahi (Environmental Management Society, Malaysia, 2007)
Air pollution in the atmosphere by TSP is a problem that has been growing for the last few years due to rapid industrialization, population growth and urbanization in the Klang Valley Region. Suspended particle levels are monitored in ambient air quality network of their potential impact on human health, visibility and climate. The objective of this study is to investigate variations and trends in TSP in the Klang Valley Region and to identify the main factors affecting the variation in TSP concentrations. This analysis used daily data collected from Malaysian Meteorological Services for Petaing Jaya station monitoring TSP data for the period 1977-2002. On daily average basis, annual, seasonal, monthly and weekly variations and trends in TSP concentrations are presented. Linear regressions were performed of the annual average TSP over the 1977 through 2002. The slope of the regression line in annual average decreased in TSP in order of -0.977 and statistically significant at 0.05 level. This suggests that whatever control measures have been applied are effective in reducing TSP concentrations. TSP concentrations in the Klang Valley Region showed seasonal variation, with the higher concentration during southwest monsoon season (dry season) and lower concentrations during rainy season. The causes of highest TSP concentrations during southwest monsoon season due to lack of rainfall and the stable atmospheric conditions, which reduce the ability of atmosphere to disperse the pollutants. The weekly pattern of TSP concentration exhibits a downward trend from Tuesday (maximum) to Sunday (minimum). This weekly cycle in TSP gives the indication that the main sources of the particulates in this area are from human activities rather than natural sources